2012
DOI: 10.5487/tr.2012.28.4.269
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hazardous Chemical Exposure on Cardiovascular Disease in Chemical Products Manufacturing Workers

Abstract: The purpose of this study was to understand the mechanism of cardiovascular disease (CVD) caused by exposure to hazardous chemicals. We investigated changes in the symptoms of metabolic syndrome, which is strongly related to CVD, and in levels of other CVD risk factors, with a special emphasis on the roles of catecholamines and oxidative stress. The results revealed that neither body mass index (BMI) nor waist and hip circumferences were associated with exposure to hazardous chemicals. Among metabolic syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, of the FRS sub-criteria, systolic blood pressure was significantly low, and HDL was significantly high. This is consistent with previous findings that heavy metals increase blood pressure and blood cholesterol levels [ 18 ]. Additionally, it has been found that total cholesterol levels are significantly higher in workers who deal with Pb [ 19 ] and that there is a significant negative correlation between PbB and HDL cholesterol levels [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, of the FRS sub-criteria, systolic blood pressure was significantly low, and HDL was significantly high. This is consistent with previous findings that heavy metals increase blood pressure and blood cholesterol levels [ 18 ]. Additionally, it has been found that total cholesterol levels are significantly higher in workers who deal with Pb [ 19 ] and that there is a significant negative correlation between PbB and HDL cholesterol levels [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…Wang et al 41 described the trend of early onset of the Stanford A dissection in 47.95 years of age and 53.37 years of age in the Stanford B dissection, which is consistent with what was observed in our study and could be related to the high levels of smoking among young people and the high levels of pollution in China. 42 , 43 The International Registry of Aortic Dissection (IRAD) demonstrates a mean age of 63 years old for Western patients with Stanford A aortic dissection. 44 …”
Section: Disscusionmentioning
confidence: 99%
“…Different types of variable risk agents (e.g lifestyle, work environment and their interaction) and non-variable risk agents (e.g sex, age, genes, etc) may be directly/indirectly associated with the prevalence of some diseases (Hong, Pedersen, Brismar, & de Faire, 1997;Kim, Won, Ko, Heo, & Chung, 2012).…”
Section: Exposure Assessmentsmentioning
confidence: 99%